Identification of potential biomarkers of porcine gelatin - Tukiran, Nur Azira; Ismail, Amin; Ghazali, Haizatul Hadirah; Mohd Ali, Nurul Azarima (Springer, 2021)
This chapter discusses the identification of potential biomarkers of porcine gelatin using peptide mass fingerprinting (PMF) for the development of anti-peptide polyclonal antibodies. The selection of antigens is a prerequisite for the development of enzyme-linked immunosorbent assay (ELISA). A synthetic peptide is one of the prevalent antigens for ELISA development. It enables the produced antibodies to be targeted at small regions of the protein with fine specificity. It has been used to solve food authenticity issues.